Development of sheep embryo in vitro: Effect of insulin or insulin-like growth factor (IGF-I) - GOEL, S; PALANISAMY, A; NAINER, A MAHALINGA (The Indian Journal of Animal Sciences, 2014)
In the present study, insulin and IGF-I was independently utilized to investigate sheep embryo development in vitro. Although the number of oocytes cleaved in both treatment groups were similar further developmetn of these to morufae or blastocysts required increased supplementation with either insulin (1-10 mg/ml) or IGF-I (2 -200ng/ml). Increase in hatched blastocyst number was also observed in these groups. The blastocyst cell number was also higher. Thus supplementation with 1mg insulin/ml or 2ng IGF-I/ml in IVC medium enhanced in vitro development of sheep embryo from 8 to 16 cell stages.